2002
DOI: 10.1093/jxb/erf035
|View full text |Cite
|
Sign up to set email alerts
|

Bleaching herbicide effects on plastids of dark-grown plants: lipid composition of etioplasts in amitrole and norflurazon-treated barley leaves

Abstract: The effects of the bleaching herbicides amitrole (125 micro M) and norflurazon (100 micro M) on etioplast lipids were studied in barley plants (Hordeum vulgare L. cv. Express) grown for 7 d either at 20 degrees C or 30 degrees C in darkness. Total lipid, glycolipid and phospholipid contents of control etioplasts were increased at 30 degrees C in comparison with those at 20 degrees C. The two herbicides caused a decrease in the total lipid, glycolipid and phospholipid amounts compared to the untreated etioplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
8
16
0
Order By: Relevance
“…These observation confirmed results reporter by Irving and coworkers (1999) who showed that norflurazon significantly increased the elongation growth of etiolated maize coleoptiles in comparison with untreated control. Thus, the effect of this chemical on plants is highly dependent on the light conditions and the differences concern mainly the structure of plastids (Pardo and Schiff, 1980;Reib et al, 1983;Di Baccio et al, 2002). Reib et al (1983) showed that cotyledons of norflurazontreated mustard seedlings grown in strong white light did not contain normal chloroplasts, but only small chlorophyll-free rudiments with completely destroyed internal structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observation confirmed results reporter by Irving and coworkers (1999) who showed that norflurazon significantly increased the elongation growth of etiolated maize coleoptiles in comparison with untreated control. Thus, the effect of this chemical on plants is highly dependent on the light conditions and the differences concern mainly the structure of plastids (Pardo and Schiff, 1980;Reib et al, 1983;Di Baccio et al, 2002). Reib et al (1983) showed that cotyledons of norflurazontreated mustard seedlings grown in strong white light did not contain normal chloroplasts, but only small chlorophyll-free rudiments with completely destroyed internal structure.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of fluridone, an herbicide also inhibiting the carotenoid synthesis, was markedly stronger on barley plastid ultrastructure in plants grown in the presence of light than in darkness (Popova, 1996). Di Baccio et al (2002) showed that norflurazon affects the level and composition of etioplast lipids. Our result proved that the metabolism of resorcinolic lipids is also under the influence of this herbicide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of PLB was severely disturbed in amitrole-treated plants, but not in norflurazon-treated plants. Because amitrole also modifies the lipid composition of membranes (Di Baccio et al 2002), it is not certain that the PLB disorganization in amitrole-treated plants is due to the accumulation of Car precursors. The type of disorganization observed is reminiscent of those observed in the ccr2 mutant of Arabidopsis (deficiency in Car isomerase), which also accumulates linear precursors (Park et al 2002).…”
Section: The Pchlide Status In Dark-grown Plant Tissuesmentioning
confidence: 99%
“…Furthermore, whether amitrole is even specific for carotenoid biosynthesis is debated. Amitrole alters root growth (Heim and Larrinua 1989), inhibits histidine biosynthesis by acting on imidazolegylcerolphosphate dehydratases from Arabidopsis and wheat (Tada et al 1995), alters lipid composition (Di Baccio et al 2002) and may alter catalase activity (Bouvier et al 1998). One report notes that substantially less amitrole is needed to inhibit root growth than carotenoid biosynthesis (Heim and Larrinua 1989).…”
Section: Introductionmentioning
confidence: 99%